(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
Tomato crop is one of the most important vegetables crops as planting ,production and export , interests in developing its cultivation and production has increased throw many methods, the most important is agricultural technology using grafted seedlings. This research was based on the study of a farm of 5 greenhouses, planted with grafted seedlings, and others planted with regular seedlings , in the village of Rahbiah – Jablah , and was based on the average prices in 2010 . This research aims to achieve the following objectives : • Analysis of the production costs of Agricultural operations for the production of tomatoes crop. • The economic evaluation for the production of tomato with grafted seedlings The study showed that the net annual income per dunum was 80929 SP In the case of regular seedlings , and 258815 SP if grafted seedlings were used. The gross margin of one dunum per year was 120222 SP in the case of regular seedlings and 295158 SP, if grafted seedlings were used, The study also showed that the overall economic efficiency of the tomato production using regular seedlings and grafted seedings was 1.4 and 2,68 respectively. يعد محصول البندورة من أهم محاصيل الخضار زراعةً و إنتاجاً و تصديراً ، و قد ازداد الاهتمام بتطوير زراعته , و زيادة إنتاجيته ، باتباع طرق عديدة أهمها ، تقنية الزراعة باستخدام الشتول المطعمة ، تم الاعتماد في هذا البحث على دراسة مزرعة خاصة مكونة من خمس بيوت بلاستيكية مزروعة بالبندورة باستخدام الشتول المطعمة ، و أخرى نفس المساحة مزروعة بالشتول العادية ، في قرية الراهبية التابعة لمنطقة جبلة . كما تم الاعتماد على متوسطات الأسعار و الأجور في عام 2010 ( قبل الأزمة ) . هدف هذا البحث إلى تحقيق الأهداف التالية: 1) تحليل التكاليف الإنتاجية لكافة العمليات الزراعية لإنتاج محصول البندورة . 2) التقييم الاقتصادي لإنتاج البندورة بالشتول المطعمة . تبين من خلال الدراسة أن صافي الدخل المزرعي للدونم سنوياً بلغ 80929 ل.س في حال استخدام الشتول العادية ، و 258815 ل.س في حال استخدام الشتول المطعمة ، كما بلغ الهامش الإجمالي للدونم سنوياً 120222 ل.س في طريقة الشتول العادية و 295158 ل.س في طريقة الشتول المطعمة . كما بينت الدراسة أن الكفاءة الاقتصادية الإجمالية لإنتاج البندورة باستخدام الشتول العادية والشتول المطعمة بلغت 1,4 و 2,68 على التوالي.